EIB Working Papers 2019/02 - How energy audits promote SMEs' energy efficiency investment (Volume 2019/2) - Revoltella, Debora (European Investment Bank, 2019)
Energy audits play an important role in promoting energy-efficiency measures in SMEs. This paper uses EIB Investment Survey data about energy audits and energy-efficiency investments of some 12,500 signatures from EU28 Member States per year. It suggests that:Energy audits are a useful tool for overcoming the information barriers and facilitating investments in energy-efficiency measuresThey are more important for small firms and for investments in things such as such as lighting, wall insulation etc. than in production processes such as the replacement of machinery and equipmentThe beneficial impact of energy audits ceases to exist, however, when firms are finance constrainedInformation campaigns are one of the most efficient available instruments among other instruments (regulatory, financial and voluntary agreements) for promoting energy audits in SMEs.